An Outlook on the Complexity of Protein Morphogenesis in Health and Disease - Brunori, Maurizio; Gianni, Stefano (Frontiers in Molecular Biosciences, 2022)
The study of the mechanisms whereby proteins achieve their native functionally competent conformation has been a key issue in molecular biosciences over the last 6 decades. Nevertheless, there are several debated issues and open problems concerning some aspects of this fundamental problem. By considering the emerging complexity of the so-called “native state,” we attempt hereby to propose a personal account on some of the key topics in the field, ranging from the relationships between misfolding and diseases to the significance of protein disorder. Finally, we briefly describe the recent and exciting advances in predicting protein structures from their amino acid sequence.